PENGARUH KETERAMPILAN MANAJERIAL KEPALA SEKOLAH DAN HUBUNGAN PELANGGAN TERHADAP MUTU LAYANAN PENDIDIKAN - Sigit Rudiyanto; Widya Kusumaningsih; Nurkolis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The quality of educational services reflects efforts to meet customer needs and expectations through accurate and effective service delivery. This study aims to: (1) determine the influence of principals' managerial skills on the quality of educational services, (2) assess the impact of customer relations on service quality, and (3) examine the combined effect of managerial skills and customer relations on educational service quality. A quantitative approach with a correlational design was employed. The population consisted of 128 teachers, with a sample of 97 selected through random sampling. Data were collected via questionnaires and analyzed using descriptive statistics, prerequisite tests (normality, multicollinearity, heteroscedasticity, linearity), and hypothesis testing through simple and multiple linear regressionThe results show: (1) a strong correlation (r = 0.823) between principals’ managerial skills and service quality, with a significant partial effect of 77.7%; (2) a strong correlation (r = 0.857) between customer relations and service quality, with a significant partial effect of 73.4%; and (3) a significant combined effect of managerial skills and customer relations on service quality, with a regression equation of Ŷ = 21.632 + 0.345X1 + 0.771X2, and a determination coefficient of 75.0%. In conclusion, both managerial skills and customer relations significantly influence the quality of educational services. It is recommended that principals enhance supervision, motivation, and coaching to improve teacher performance and service outcomes.